Characterization of Eichhornia crassipes bio-adsorbent activated by H3PO4 for the removal of lead ion (Pb2+) from wastewater of battery industry - Erlangga, Reza; Sari, Dessy Agustina; Wahyuningtyas, Aulia (Universitas Mercu Buana, 2025)
Lead ion (Pb2+) contamination from battery industry wastewater affects significant environmental and health risks. This study explored the use of H3PO4-activated water hyacinth (WH) bio-adsorbent as an effective solution for removing Pb2+. The WH bio-adsorbent was prepared by activating dried water hyacinth stems with 1.2 M H3PO4, enhancing adsorption properties. SEM-EDX analysis revealed significant morphological changes, with increased porosity and oxygen-containing functional groups (O-H, C-O-P), which improved adsorption capacity. Adsorption kinetics followed a pseudo-second-order model (R2 = 0.99981), indicating that chemisorption dominated the Pb2+ removal process. Adsorption isotherms firmly fit the Langmuir model (R2 = 0.96), confirming monolayer adsorption on a homogeneous surface. The effect of pH was also investigated, with maximum adsorption efficiency (96.928%) observed at pH 7. FTIR analysis showed changes in functional groups before and after adsorption, confirming the ion exchange mechanism between Pb2+ and the activated bio-adsorbent. The findings suggest that H3PO4 activation increases the surface area and raises the chemical activity of WH, providing new insights into the dual mechanism of physical and chemical modifications for lead removal. This study addresses a critical gap in optimizing adsorbents for heavy metal removal, demonstrating the potential of H3PO4-activated WH for industrial wastewater treatment.